Changes in Palm Temperature as Predictor of Long-term Cure of Sympathicotomy for Palmar hyperhidrosis? - Liu, Gaoli; Kang, Ganjun; Huang, Jie; Xie, Songping; Hu, Haifeng (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Objectives To investigate the long-term relationship between intraoperative temperature changes of the palm, treatment effects and compensatory hyperhidrosis (CH).Methods We retrospectively analyzed the data of 41 patients with palmar hyperhidrosis who underwent bilateral endoscopic sympathicotomy 3 to 6 years ago. Before and after the operation, changes in ipsilateral palm temperature were monitored and recorded to evaluate the curative effect of the sympathicotomy.Results All operations were performed successfully. Concerning cure, there was no statistically significant difference between patients with different maximum temperature (Tmax) values (p = 0.455). There was a very weak correlation between postoperative palm temperature (34.309 ± 1.377°C) (p = 0.049; correlation coefficient − 0.218). The T3 + T4 sympathicotomies had a higher Tmax (p = 0.000). The incidence and degree of CH had no relationship with Tmax in the left (p = 0.266 and p = 0.168, respectively) or the right hand (p = 0.640 and p = 0.824, respectively).Conclusions Temperature change has a relationship with surgery, but it cannot directly predict the long-term curative effect of a sympathicotomy or the occurrence of CH. Additional studies are required.
Keywords: palmar hyperhidrosis; sympathicotomy; temperature; thoracoscopy